The Effects of Climate and Anthropogenic Activity on Hydrologic Features in Yanhe River - Yang Cheng; Hongming He; Nannan Cheng; Wenming He (Advances in Meteorology)
This paper aims to analyze the effects of precipitation and anthropogenic activity on hydrologic features in Yanhe River so as to provide support for regional water management and evaluation of water and soil conservation measures. Thiessen Polygon was created to calculate mean values of watershed, and Mann-Kendall statistic test and Sen’s slop estimator test were adapted to analyze variation trend and interaction between precipitation, runoff, and sediment discharge. When 1961~1970 was set as reference period (ignoring human effects), the double mass curve quantified the effects of precipitation and anthropogenic activity on runoff and sediment discharge in Yanhe River during 1961~2008. The result showed that the monthly distribution of precipitation, runoff, and sediment discharge was extremely uneven. 78.1% of precipitation, 64.1% of runoff, and 98.6% of sediment discharge occurred in the flood season. Precipitation, runoff, and sediment discharge performed significant downward trends during 1961–2008. Therein, anthropogenic factors contributed 66.7% and 51.1% to sediment discharge reduction during 1971–1994 and 1995–2008, respectively. They contributed 103.8% and 82.9% to runoff reduction during these two periods, respectively.